Measures for diffusion of solar PV in selected African countries. Issue 7 (9th August 2017) - Nygaard, Ivan; Hansen, Ulrich Elmer; Mackenzie, Gordon; Pedersen, Mathilde Brix
ABSTRACT: This paper investigates how African governments are considering supporting and promoting the diffusion of solar PV. This issue is explored by examining so-called 'technology action plans (TAPs)', which were main outputs of the Technology Needs Assessment project implemented in 10 African countries from 2010 to 2013. The paper provides a review of three distinct but characteristic trajectories for PV market development in Kenya (private-led market for solar home systems), Morocco (utility-led fee-for service model) and Rwanda (donor-led market for institutional systems). The paper finds that governments' strategies to promoting solar PV are moving from isolated projects towards frameworks for market development and that there are high expectations to upgrading in the PV value chain through local assembly of panels and local production of other system elements. Commonly identified measures include support to: local production; financing schemes; tax exemptions; establishment and reinforcement of standards; technical training; and research and development.